Motivation, Environment, and Culture as Determinants of Employees’ Performance at Maya Ubud Resort and Spa - Bidari, Ni Putu Intan; Irwansyah, M. Rudi; Trianasari (Yayasan Ilomata, 2025)
Employee performance is a critical factor in ensuring service quality within the hospitality industry, particularly in luxury resort settings where expectations are high. However, limited research has examined how internal organizational factors influence performance in this context. This study aims to examine the effect of work motivation, work environment, and organizational culture on employee performance at Maya Ubud Resort and Spa in Bali. A quantitative method was employed, using data collected from employees with a minimum of two years of tenure through a structured questionnaire. The results indicate that work motivation and work environment both have a positive and significant impact on employee performance, while organizational culture does not show a significant direct effect. The model developed in this study explains approximately 82% of the variance in employee performance. These findings suggest that enhancing motivation and improving work conditions are essential for boosting employee effectiveness. Although organizational culture did not exhibit a direct influence, its potential long-term or indirect effects may be relevant for further study. The research offers practical insights for human resource development in the hospitality sector, particularly in designing strategies that align internal organizational factors with employee performance improvement goals.